Adhesive bond potential of compressed stabilised earth brick. (February 2020) - Kolawole, John Temitope; Olalusi, Oladimeji Benedict; Orimogunje, Ademola Johnson
Abstract: Huge embodied energy, carbon footprint and cost of fired brick gave way for compressed stabilised earth bricks (CSEB). However, in order to improve its surface erosion durability, another problem arose due to CSEB plastering, which is poor long-term bonding. This problem gave rise to this research aimed at investigating and improving the adhesive bond between mortar and compressed stabilised earth bricks. Four variants of CSEB were made from inclusions of sand and used motor oil while six variants of mortar containing cement, sand, used motor oil and earth were used. Sandcrete block served as the control. Dry and wet shear bond strengths between the CSEBs and mortars were determined by an innovative loading system. The results from the investigation show that the inclusion of sand and oil in CSEB improved the dry unconfined strength by 88.2% but reduced the wet unconfined strength by 19.5%. The inclusion of sand and oil has relatively no impact on the water absorption properties of CSEB. All four variants of CSEB have the best bond with cement mortar in dry condition but worst bond under wet condition. Cement mortar containing earth/and oil have the best bond with the four variants of CSEB in wet condition. This study concludes that CSEB plaster should contain earth in the right proportion to avoid spalling associated with plastered CSEB in water prone surfaces. Also, sand and used motor oil can be included in CSEB for heavy load masonry works.